A Critical Mutualism – Competition Interplay Underlies the Loss of Microbial Diversity in Sedentary Lifestyle - Castellanos, Nazareth; Diez, Gustavo G.; Antúnez-Almagro, Carmen; Bailén, María; Bressa, Carlo; González Soltero, Rocío; Pérez, Margarita; Larrosa, Mar (Frontiers in Microbiology, 2020)
Physical exercise improves the overall health status by preventing the development of several diseases. In recent years, it has been observed that physical exercise impacts gut microbiota by increasing the presence of beneficial bacteria and microbial diversity. In contrast, a sedentary lifestyle increases the incidence of chronic diseases that often have an associated loss of microbial diversity. The gut microbiota is a vast ecosystem in which microorganisms interact with each other in different ways; however, microbial ecosystem interactions are scarcely studied. The goal of this study was to determine whether individuals with a sedentary lifestyle have lower diversity in their gut microbiota and how microbial diversity is associated with changes in bacterial network interactions. For that purpose, diet, body composition, physical activity, and sedentarism behavior were characterized for individuals who did or did not comply with the World Health Organization recommendations for physical activity. The composition of the gut microbiome was determined by 16S rRNA gene sequencing. Reorganization of microbial structure with lifestyle was approached from network analysis, where network complexity and the topology of positive and negative interdependences between bacteria were compared and correlated with microbial diversity. Sedentary lifestyle was significantly associated with a diet low in fiber and rich in sugars and processed meat, as well as with high visceral and total corporal fat composition. The diversity (phylogenic diversity, Chao, observed species and Shannon’s index) and network complexity of the gut microbiota were significantly lower in sedentary compared to active individuals. Whereas mutualism or co-occurrence interactions were similar between groups, competitiveness was significantly higher in the active lifestyle group. The mutualism-competition ratio was moderate and positively associated with diversity in sedentary individuals, but not in active individuals. This finding indicates that there is a critical point in this ratio beyond which the stability of the microbial community is lost, inducing a loss of diversity.